FORMULATION OF CRIMINAL LAW POLICY REGARDING NIHIL VERDICTS IN INDONESIAN CRIMINAL COURTS - Hensi Septia Utami; Nurini Aprilianda; Faizin Sulistio (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The verdict of acquittal in the application of law enforcement still has problems, namely the existence of a conflict of norms or a regulatory gap, whereby Article 193 of the Criminal Procedure Code "orders" judges to impose a sentence if the defendant is proven guilty. However, Article 67 of the Criminal Code, which refers to the types of basic penalties in Article 10 of the Criminal Code, "prohibits" the imposition of penalties if the defendant has already been sentenced to death or life imprisonment. This conflict of norms or regulatory gap creates a dilemma for judges in enforcing the law. This research is a normative type of research , using a statute approach, a conceptual approach, and a case approach, as well as primary, secondary, and tertiary law, and a prescriptive analysis method. This study discusses two main issues, namely the Regulation of Nil Verdicts in Indonesian Criminal Procedure Law and the Ideal Regulation Related to the Concept of Nil Verdicts in Indonesian Criminal Procedure Law in the Future.